Brain connectivity by single-photon emission computed tomography and graph theory: a mini-review - Carlos A. Sanchez-Catasus; Karla Batista-García-Ramó; Lester Melie-Garcia (Academia Medicine)
Current neuroimaging technologies play an important role in neurological disorders. Among these technologies, nuclear medicine neuroimaging such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) play a key role. The relevance of brain SPECT is that it has lower costs and greater availability compared to brain PET. Quantitative methods used in brain SPECT are generally univariate. The main limitation of these methods is that they do not allow investigating the relationship between brain regions (i.e. connectivity). One of the multivariate methods that has proven to be useful is graph theory. In this article, we review brain connectivity modeling based on this approach applied to brain SPECT. We also include some clinical studies to illustrate the potential of this method to detect subtle changes in brain connectivity. Recent advancements in new SPECT technology detectors could be the basis for the next level of use of this analysis methodology in the near future.